Welfare level of Troll Line Fishermen in Pasokan Village - Ratni Dg Mareto; Aziz Salam; Alfi Sahri Baruadi (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This paper aims to describe the welfare level of troll fishermen in Supply Village, Walea Besar Subdistrict, Tojo Una-una District, Central Sulawesi Province. Respondents' income and expenditure are measured and then analyzed to determine the level of welfare using BPS Criteria. On average 84% of fishing families are prosperous and 16% of families with low welfare. Age, education, fishing experience and number of family members are factors that affect the level of welfare. Keywords: welfare; .fishermen; troll line